Task analysis - A case study of the women's ST development team - Hamelin, Y. (2009)
How much training volume is required to achieve elite performance? What critical gaps in athletic skill development exist? Sébastien Cros, National Team Coach, Short Track, will walk participants through a demonstration of how he has used LTPAD recommended training volumes to determine the preparation objectives of athletes both in terms of training volume and prioritisation of skills development with the context of yearly training plan.